Effect of Groundnut Plant Residues on Germination and Radicle Elongation of Four Crop Species - Wahab, Zakaria; Razak, Abdul Rahman (1990)
Groundnut (Arachis hypogaea L.) )yield has been reported to decrease by more than 50% with successive croppings. Filtrates from fresh and decomposed groundnut plant residues were bioassyed for their effects on germination and radicle elongation of four crop species. Results obtained indicated that the inhibitory substance(s)present in the residues is soluble in water; heat treatment or prolonged decomposition seemed 10 reduces or possible eliminate the inhibitory activity of the residues. The production of the inhibitor(s) also seem to follow a cycle and may also be associated with changes in pH of the residue filtrates.Delaying D planting of the subsequent crop is suggested as a precaution against poor germination and early growth if plant residue Were incorporated or left on Ihe soilsurface after harvest.